Mangrove Ecosystem Management for Sustainable Renewable Energy Production: A Multi-Dimensional Analysis - Hanifah, Abu; Sukendi, Sukendi; Thamrin, Thamrin; Putra, Ridwan Manda (International Journal of Energy Economics and Policy, 2023)
Mangrove ecosystems have become a critical habitat for sustaining renewable energy production, and their management is essential to maintain their ecological, economic, and social functions. This study aimed to analyze the multidimensional aspects of mangrove ecosystem management for sustainable renewable energy production in the Tebing Tinggi, Kepulauan Meranti, Riau. This study formulates sustainable management schemes for the mangrove ecosystem in the Tebing Tinggi, Kepulauan Meranti, Riau by analyzing the ecological, economic, social, legal-institutional, and technological aspects of the ecosystem. To conduct this analysis, researchers used the Multidimensional Scaling (MDS) approach, which relies on an algorithm called the MDS algorithm. The findings from the study reveal that the use of mangroves can increase people’s income, but the level of community education is still low, and there is a lack of community participation in mangrove ecosystem management activities. Based on the Rap-Mangrove analysis, the multidimensional index of mangrove ecosystem management is considered sufficiently sustainable. The findings emphasized the significance of community participation and education in managing mangrove ecosystems. The study concludes that sustainable management schemes for mangrove ecosystems are necessary to ensure their continued contribution to renewable energy production.